Determination of cortisol in Oreochromis sp. plasma using the RP-HPLC (reverse phase –high performance liquid chromatography) - Thang, Nguyen Quoc; Tan, Le Van; Thanh Huong, Le Thi; Kim Phuong, Nguyen Thi (Vietnam Journal of Chemistry, 2016)
Cortisol is a hormone which was generated in adrenal gland. Its characteristics have been known as fight off stress, inflammation, allergy, increase of transforming carbohydrate, lipid, and protein. A simple isocratic reverse-phase high-performance liquid chromatography procedure was developed to quantify plasma cortisol. The cortisol was extracted from 500µL Oreochromis sp plasma with 5000 µL of dichloromethane, washed in 5000 µL of sodium hydroxide (0.1 M)  before a final drying step and reconstitution in mobile phase for injection. Separation was achieved using a hypersil BDS-C18, 4.0 × 125 mm, 5 µm particle size, at 36°C, with Diode Array Detector set at 254 nm. The mobile phase consisted of 45% methanol in water, set at a flow rate of 0.8 mL/min. The linear range was collected from 50 to 250 ng/mL, with linear regression A = 0.05547C + 0.05246, correlation coefficient R = 0.99996. The limit of detection (LOD) and limit of quantification (LOQ) were 0.87 ng/mL and 2.9 ng/mL, respectively. The recovery was 93.9%. Concentrations of cortisol in plasma ranged from 54.0 to 104.5 ng/mL. A method using RP-HPLC/UV is proposed that was shown to be sensitive and specific for the determination of plasma cortisol for environmental toxicology study purposes. Keywords. Cortisol, high-performance liquid chromatography, oreochromis sp.